AN ANALYSIS OF STUDENTS' DIFFICULTIES IN WRITING RECOUNT TEXT (A CASE STUDY AT A SENIOR HIGH SCHOOL IN INDRAMAYU) - Ida Yulianawati (Jurnal Bahasa Inggris, 2018)
This study investigates students? causes of students? difficulties, kinds of students? difficulties, and the most dominant problem in writing recount text written by ten students at a Senior High School in Indramayu, West Java. This study employed a qualitative research design, embracing characteristics of a case study. The data were obtained from collection of samples of students? recount texts. The findings revealed that most students have been able to implement the schematic structures and linguistic features of argumen texts, which indicates the ability of students to write the texts and to achieve its purpose. However, some students found difficulties in terms of the use of tenses, the use of vocabulary, and the use of specific participants. Based on the analysis of students? writing, it was found some causes that made students did some mistakes in writing recount texts. Based on these findings, it is recommended that explicit teaching be needed to develop students? writing skills.